A new cumulative damage model for time-dependent reliability analysis of deteriorating structures. (April 2020) - Li, Junxiang; Chen, Jianqiao; Chen, Zhiqiang
Performance and reliability of structures will deteriorate with the effects of loads, environment, and interior factors of materials. In this article, a novel cumulative damage model is developed for time-dependent reliability analysis of deteriorating structures. The deterioration is a combination of three stochastic processes: the gradual deterioration posed by aging effects, the sudden deterioration caused by transient loads, and the additional deterioration introduced by sustained loads. The aging effect is modeled as a gamma process, while the transient load is described by a Poisson process. The sustained load is modeled by a stationary binomial process and a Poisson square wave process, respectively. The load threshold for three different scenarios are all considered and applied to not only the transient loads but also the sustained loads. The time-dependent reliability of deteriorating structures is then evaluated based on this model via semi-analytical methods or numerical simulation methods. Three numerical examples and an example involving a natural gas pipeline are used to validate the effectiveness of the proposed model for computing the time-dependent reliability.